2019
DOI: 10.3389/fevo.2019.00406
|View full text |Cite
|
Sign up to set email alerts
|

Papillomavirus in Wildlife

Abstract: Papillomaviruses (PV) are associated with epithelial malignancies in animals, including cancer in humans. Limited knowledge exists regarding the evolutionary history of non-human PV. We assessed the phylogeography of PV with emphasis in wildlife hosts. We explored the phylogenetic, geographic, and environmental relationships of PV and hosts applying Bayesian inference and spatial analyses of virus and hosts. We found that the available wildlife PV data support previous reports on the higher incidence of fibrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 88 publications
0
16
0
Order By: Relevance
“…Cutaneous papillomas and fibropapillomas have been reported in several cervids species. These skin tumors have been repeatedly associated with species-specific PV, although this association might be more complex than previously considered (14). Genomes of deer-(White-tailed deer, Odocoileus virginianus) (26), Reindeer-(Rangifer tarandus) (10), European Elk-(Alces alces) (27), Roe deer-(Capreolus capreolus) (15), and Red deer-(Cervus elaphus) papillomavirus (12) have been sequenced and they have all been demonstrated to be member of the Delta-papillomavirus genus.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Cutaneous papillomas and fibropapillomas have been reported in several cervids species. These skin tumors have been repeatedly associated with species-specific PV, although this association might be more complex than previously considered (14). Genomes of deer-(White-tailed deer, Odocoileus virginianus) (26), Reindeer-(Rangifer tarandus) (10), European Elk-(Alces alces) (27), Roe deer-(Capreolus capreolus) (15), and Red deer-(Cervus elaphus) papillomavirus (12) have been sequenced and they have all been demonstrated to be member of the Delta-papillomavirus genus.…”
Section: Discussionmentioning
confidence: 97%
“…Papillomas and fibropapillomas have been reported in a wide range of domestic and wild animals including several cervid species, such as white-tailed (Odocoileus virginianus) and mule deer (Odocoileus hemionus) in North America (8), European elk (Alces alces) (9) and reindeer (Rangifer tarandus) in Sweden (10), red deer (Cervus elaphus) in Scotland (11), as well as red deer and roe deer (Capreolus capreolus) in Hungary (12,13). Speciesspecific papillomaviruses (PV), whose origin has been recently traced to the European continent (14), were frequently detected in association with these tumors. Fibropapillomas in roe deer most commonly develop on the skin of the head, neck, abdomen and limbs of the affected animal (15).…”
Section: Introductionmentioning
confidence: 99%
“…The traditional PV types within a species share between 71 and 89% nucleotide identity within the complete L1 ORF [41]. Most of the effort applied to understand the evolution of PVs and their classification has been focused on HPVs and PVs in domestic animals, such as BPV types [10]. There are limited studies available concerning PVs from wildlife hosts [42,45], representing a gap in knowledge regarding our understanding of the evolution and diversification of PVs in the wild [10].…”
Section: Discussionmentioning
confidence: 99%
“…Most of these viruses are species-specific [5,6], but cross-infections have also been reported [5,[7][8][9]. It was reported that some animal species are often infected by PVs belonging to different taxonomic groups [10][11][12]. Cross-infections with Deltapapillomavirus BPV-1, BPV-2 and CePV-1 have been identified in the healthy skin of wild ruminants, and cross-infections with BPVs from the genus Xipapillomavirus have been identified, both as single infections and in association with Deltapapillomavirus BPV-1 and BPV-2 [13,14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation